Answer:
[tex]cos(5x^2) = \sum_{k=0}^{\infty} \frac{(-1)^k 5^{2k}x^{4x}}{(2k)!} = 1 - 25\frac{x^4}{2}+625\frac{x^8}{24}+....[/tex]
And it converges at [tex](-\infty,\infty)[/tex]
Step-by-step explanation:
Remember that in general the taylor series of cosine is given by
[tex]cos(x) = \sum_{k=0}^{\infty} \frac{(-1)^k x^{2k}}{(2k)!}[/tex]
and it converges at [tex](-\infty , \infty )[/tex].
therefore
[tex]cos(5x^2) \\= \sum_{k=0}^{\infty} \frac{(-1)^k (5x^2)^{2k}}{(2k)!}\\= \sum_{k=0}^{\infty} \frac{(-1)^k 5^{2k}x^{4x}}{(2k)!}\\\\= 1 - 25\frac{x^4}{2}+625\frac{x^8}{24}+....[/tex]
And it also converges at [tex](-\infty,\infty)[/tex]